Digitalization of Private Islamic Universities in West Java: A Case Study of Leadership and Transformation - Rosyad, Ramlan; Wahyudin, Dinn; Norman, Efrita; Karim, Abdul; Dewi, Maftuhah; Ropitasari, Anna (LP. Ma'arif Janggan Magetan, 2025)
This research examines the role of transformational leadership in driving digitalization at Universitas Islam Bunga Bangsa Cirebon (UI BBC) in West Java, Indonesia. Private islamic universities in indonesia face challenges in adopting digital technology due to limited resources and infrastructure. However, digitalization provides a great opportunity to improve education quality and administrative efficiency. UI BBC successfully transitioned from manual to digital systems thanks to the visionary leadership of the rector who was able to motivate the academic community. This research uses a qualitative approach with a case study, collecting data through in-depth interviews, observation, and documentation analysis. The findings show that transformational leadership plays an important role in developing digital infrastructure and improving digital literacy. Despite budget constraints, UI BBC successfully developed an integrated learning and administration platform. This research suggests that the transformational leadership model at UI BBC is a reference for other private Islamic universities and the importance of policy support from the government.